VALIDATION INFORMATION SYSTEM FOR MOBILE-BASED PROPOSAL SEMINAR REGISTRATION - Sinaga, Imam Adlin; Fakhriza, M.; Takhir, Said Hambali (ZERO: Jurnal Sains, Matematika dan Terapan, 2023)
The information systems study program at the Faculty of Science and Technology is one of the study programs at the State Islamic University of North Sumatra, Medan. As a study program in the field of computer technology, the information systems study program has an important role in efforts to develop knowledge in the field of computer technology as demanded by national digital literacy. There are several problems in the registration system for proposal seminars in the information systems study program at the Faculty of Science and Technology due to the lack of performance of the system. The purpose of this research is to build a mobile-based information system that can be used to validate the proposal seminar registration that has been conducted by students. The system development method used is waterfall, while in making a visual system design, the author uses UML (Unified Modeling Language). In developing the information system, the author uses Kodular tools and the Google Spreadsheet database. With this information system, it is hoped that it can assist students in registering for proposal seminars and assist study program admins in validating proposal seminar registrations that have been carried out by students easily and quickly via mobile android.